2013
DOI: 10.1371/journal.pone.0055487
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Mechanism of Inhibition of Dendritic Cells Maturation by Mesenchymal Stem Cells via Interleukin-10 and the JAK1/STAT3 Signaling Pathway

Abstract: Mesenchymal stem cells (MSCs) can suppress dendritic cells (DCs) maturation and function, mediated by soluble factors, such as indoleamine 2,3-dioxygenase (IDO), prostaglandin E2 (PGE2), and nitric oxide (NO). Interleukin-10 (IL-10) is a common immunosuppressive cytokine, and the downstream signaling of the JAK-STAT pathway has been shown to be involved with DCs differentiation and maturation in the context of cancer. Whether IL-10 and/or the JAK-STAT pathway play a role in the inhibitory effect of MSCs on DCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 35 publications
7
72
0
4
Order By: Relevance
“…As described above, MSCs can suppress dendritic cell maturation and function, mediated by soluble factors which also include IDO. It was demonstrated that MSCs inhibit the maturation of DCs through the stimulation of IL-10 secretion and by activating the JAK1 and STAT3 signaling pathway [186] .…”
Section: Indoleamine-23-dioxygenasementioning
confidence: 99%
“…As described above, MSCs can suppress dendritic cell maturation and function, mediated by soluble factors which also include IDO. It was demonstrated that MSCs inhibit the maturation of DCs through the stimulation of IL-10 secretion and by activating the JAK1 and STAT3 signaling pathway [186] .…”
Section: Indoleamine-23-dioxygenasementioning
confidence: 99%
“…Such IL-10 levels may simply be the sum of the individual production of IL-10 by MSCs and tumor cells in cocultures with NCx-MSCs, but in those with BM-MSCs or CeCa-MSCs, where the IL-10 production was higher than the proper sum of the individual cell types, these differences could be the result of the cross talk between CaSki and MSCs during cell coculture through transwell plates, as recently was reported by Liu and cols. [45], who found that ratderived BM-MSCs increased the IL-10 intracellular expression after transwell cell coculture with dendritic cells, suggesting MSC activation in such cell cocultures. In this regard and in trying to determine which is the source of the IL-10 in our cocultures, we have observed, in preliminary assays, that BM-MSCs and CeCa-MSCs in coculture with CaSki cells increased the IL-10 intracellular expression in comparison with their respective monocultures, however, it is possible also that CaSki cells increase IL-10 expression; these two aspects are under investigation.…”
mentioning
confidence: 99%
“…Введенные локально, МСК привлекают макрофаги и способствуют их по-ляризации в регуляторный фенотип [16]. Более того, фагоцитоз фрагментов погибших МСК ма-крофагами стимулирует их регенеративную и им-муномодулирующую функцию [38]. Влияние MСК на функцию макрофагов и остеокластов имеет важное значение для оценки целесообраз-ности использования этих клеток-предшествен-ников при создании биоимплантатов костей [18].…”
Section: роль мск в ремоделировании костной тканиunclassified
“…Современные стратегии создания ткане-инженерных конструкций активно используют МСК для улучшения интеграции имплантатов и предотвращения иммунологического отторже-ния. В доклинических исследованиях показано, что заселение биосовместимых материалов МСК значительно повышает остеокондуктивность и улучшает интеграцию имплантатов [30,38]. Первые клинические испытания скаффолдов, заселенных МСК, подтверждают их эффектив-ность [20].…”
Section: заключениеunclassified
See 1 more Smart Citation